The role of third-party funds on the effect of intellectual capital and zakat performing ratio on firm performance in Islamic banks - Maya Novitasari; Richo Diana Aviyanti; Wan Adiba Wan Ismail (Journal of Islamic Accounting and Finance Research, 2022)
Purpose - This study aimed to examine the effect of intellectual capital and zakat performing ratio on the firm performance of Islamic Banks with third-party funds as the moderating variable.Method - This study included all Islamic Banks registered with the Financial Services Authority (OJK) from 2014 to 2020 which were selected using a purposive sampling method that included financial and annual reports, yielding 77 companies as samples. Data were obtained from the Indonesia Stock Exchange and tested using SPSS.Result - The results showed that intellectual capital has a positive effect on ROA and ROE, while the zakat performing ratio has no effect on ROA and ROE. The results showed that third-party funds cannot moderate the effect of intellectual capital on firm performance, and third-party funds cannot moderate the effect of the zakat performing ratio on firm performance.Implication - In order to improve firm performance, Islamic Banks in Indonesia must focus on factors that can increase customer and prospective customer trust in Islamic Banks.Originality - This study used third-party funds as a moderating variable to complete the research gap on the effect of intellectual capital and the zakat performing ratio on firm performance.